Designing an interactive map for mosque tour guide / Nurwahidah Ab Aziz - Ab Aziz, Nurwahidah (2020)
Mosque Tourism has grown rapidly due to the variety of attractions offered. There are several factors that affect tourists visiting a mosque such as the desire to know about Islam, the uniqueness of architecture and history of mosque. However, some of mosques are still using deliver method such as lecture, storytelling and guided tours sessions during Mosque Tour Guide (MTG) program. Aim of this study is to produce an interactive map for MTG program. To achieve the aims, the objectives of this study are: 1) To develop a tool that can help volunteer in delivering information relates to spatial component in mosque to visitors, 2) To evaluate user satisfaction while using interactive map. This study was conducted at four mosques which National mosque, Federal Territory mosque, Jamek mosque and Muhammadi mosque but it was just focussing at Jamek mosque. The data that needed to be collect were the information, floor plan and image of the spatial component of each mosque. The software use is ArcGIS, Adobe Photoshop and Adobe Flash. The methodology adopted for this study is a mixed method approach such as in- situ observation and in depth interviews with the volunteers. In this research, Adobe Flash software were used to create an interactive map that relates to component in mosque for MTG program. Target users of this project will be mainly tourist either from local or abroad whom are not familiar and want to know about that mosque. This interactive map will act as a navigation map that allows users to explore and know a little about mosque information as well as to facilitate volunteers in the transmission of information. The value of this study to achieve the 'Mosque Trail in Malaysia' and to promote the mosque tourism in Malaysia.